Rosiglitazone induces apoptosis on human bladder cancer 5637 and T24 cell lines - Xu, Xiaoyuan (Int J Clin Exp Pathol, 2017)
Rosiglitazone is a synthetic ligand of peroxisome proliferator-activated receptor γ (PPARγ), and it can induce apoptosis and autophagy in a variety of cancer cells. In the present study, we aimed to investigate the influence of rosiglitazone on the proliferation and apoptosis of the 5637 and T24 human bladder cancer cell lines. The results demonstrated that the level of growth inhibition rate was gradually increased by treating the 5637 and T24 cells with higher doses of rosiglitazone and longer incubation time. Rosiglitazone exerted a potent inhibiting effect on migration of the 5637 and T24 cell lines. Moreover, rosiglitazone exerted a antineoplastic activity by inducing apoptosis and cell cycle arrest. Furthermore, treatment with rosiglitazone led to decrease the anti-apoptotic protein Bcl-2 level and increase the pro-apoptotic protein caspase 3 level in 5637 and T24 cells. Importantly, the protein expression of PPAR γ was significantly increased in the present of rosiglitazone in 5637 and T24 cells as compared to control group. In conclusion, the present study demonstrates that rosiglitazone has a potential antineoplastic activity in human bladder cancer cell lines, and the underlying mechanism was mediated, at least partially, through regulation of apoptosis-related protein and PPAR γ expression.